Konsep Tarbiyah, Ta’lim, dan Tadris dalam Al-Qur’an - Muhammad Irfansyah Siregar; Radhinal Abdullah; Asnil Aidah Ritonga; Mohammad Al Farabi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The problem in this research is the discovery of errors in interpreting the concepts of tarbiyah, ta'lim and tadris in the world of education. The Al-Quran explains the many meanings of these tarbiyah, ta'lim and tadris. The aim of this research is to discuss the meaning of the concepts of tarbiyah, ta'lim and tadris contained in the Al-Qur'an in order to provide a very relevant understanding. The theories used are the concepts of tarbiyah, ta'lim and tadris. Data collection for this research used qualitative methods which were carried out by means of literature studies taken from several tafsir books, journals and other sources relevant to the topic. The results of this research are that the tarbiyah concept is aimed at an educator to teach step by step following one process after another. This concept term is often used in the world of undergraduate education. The concept of ta'lim itself tends to provide knowledge at an adult level or in other terms, knowledge transfer. This concept is often used in study groups. Meanwhile, the concept of ta'lim is often used in formal education, as this concept involves students, an educator is only a guide and director.